2021
DOI: 10.31663/tqujes.11.2.390(2021)
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Vibration of Cracked Graded Rayleigh Beam with Axial Motion

Abstract: The paper presents the transverse vibration of an open edge crack graded Rayleigh beam with axial motion. The vibration equation was obtained relying on Hamilton's precept and resolved by the approach of Galerkin's. The power-law is adopted to represent the gradient of properties of the material composing the beam along the direction of the thickness. Cracks were modeled as rotational massless spring. The effects of axial velocity, material property change index, location, and depth of cracking on the vibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It was shown that the finite difference method could effectively and efficiently be used to study the dynamic response of moving beams. While applying the distribution of power law, dynamic analysis of edge cracks moving beam was presented in [13]. The findings demonstrate growth in the crack depth, and an increase in the speed of the beam results in a significant drop in the natural frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the finite difference method could effectively and efficiently be used to study the dynamic response of moving beams. While applying the distribution of power law, dynamic analysis of edge cracks moving beam was presented in [13]. The findings demonstrate growth in the crack depth, and an increase in the speed of the beam results in a significant drop in the natural frequencies.…”
Section: Introductionmentioning
confidence: 99%